An Analysis Types of Figurative Languages Used in The Sherlock Holmes; The Adventure of Sherlock Holmes of The Noble Bachelor - Talita Gabriel Adventalia; Susanty; Ristati (The Study Program of English Education of Palangka Raya University, 2022)
The objectives of this research are to describe the types of figurative languages found in the short story, identify the meaning of the figurative languages, and find the most frequently used figurative language type in the story. The method used in this research is descriptive analysis. The data were collected from the adventure of noble bachelor short story. The research has found 41 figurative languages of 8 types, which are 21 metonymy (51.21%), 6 hipflask (14.63%), 4 epithet (9.76%), 3 synecdoche (7.32%), 2 metaphor 2 (4.88%), simile 2 (4.88%), irony 2 (4.88%), and innuendo (2.44%). The research has found that metonym used more than other figurative languages and the contextual meaning are used in the short story.